Taxonomic novelties in Magnolia-associated pleosporalean fungi in the Kunming Botanical Gardens (Yunnan, China) - Dhanushka N. Wanasinghe (2020)
© 2020 Wanasinghe et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. This paper represents the first article in a series on Yunnanese microfungi. We herein provide insights into Magnolia species associated with microfungi. All presented data are reported from the Kunming Botanical Gardens. Final conclusions were derived from the morphological examination of specimens coupled with phylogenetic sequence data to better integrate taxa into appropriate taxonomic ranks and infer their relationships. Shearia formosa, the type species of Shearia, lacks type material, and its phylogenetic position accordingly remains unresolved. A fresh collection of Shearia formosa, obtained from Magnolia denudata and M. soulangeana in China, therefore, designated a neotype for stabilizing the application of the species and/or genus name. Phylogenetic analyses of a combined DNA data matrix containing SSU, LSU, RPB2 and TEF loci of representative Pleosporales revealed that the genera Crassiperidium, Longiostiolum and Shearia are a well-defined monophylum. It is recognized as the family Longiostiolaceae and strongly supported by Bayesian and Maximum Likelihood methods. Its members are characterized by immersed to semi-immersed, globose to subglobose ascomata with a central, periphysate ostiole, a peridium composed of rectangular to polygonal cells, cylindrical to clavate asci, broadly fusiform, hyaline to pale brown ascospores, a coelomycetous asexual morph with pycnidial conidiomata, enteroblastic, annellidic, ampulliform, doliiform or cylindrical conidiogenous cells and cylindrical to fusiform, transverse and sometimes laterally distoseptate conidia without a sheath or with a basal lateral sheath. Nigrograna magnoliae sp. nov. is introduced from Magnolia denudata with both asexual and sexual morphs. We observed the asexual morph of Brunneofusispora sinensis from the culture and therefore amended the generic and species descriptions of Brunneofusispora.